Physiological and metabolic responses of wheelchair athletes in different racing classes to prolonged exercise - Campbell, I. G.; Williams, C.; Lakomy, H. K. (Journal of Sports Sciences, 2004)
The aims of this study were to examine and compare selected physiological and metabolic responses of wheelchair athletes in two paraplegic racing classes [T3: n = 8 (lesion levels T1-T7; paraplegics); T4: n = 9 (lesion levels below T7; paraplegics)] to prolonged exercise. In addition, we describe the responses of three tetraplegic athletes [T2: n = 3 (lesion levels C6/C7: tetraplegics)]. Twenty athletes completed 90 min of exercise at 75% VO2peak on a motorized treadmill adapted for wheelchairs. The mean (+/- s) heart rates of the T3 and T4 racing classes were 165 +/- 2 and 172 +/- 6 beats.min-1, respectively. For the T4 racing class, heart rate gradually increased during the test (P < 0.05), whereas for the T3 racing class, heart rate reached a plateau after an initial increase. The mean heart rate of the tetraplegics was 114 +/- 3 beats.min-1. The T3 and T4 classes exhibited similar respiratory exchange ratios, plasma lactate and glucose concentrations throughout the test. For both the T3 and T4 racing class, free fatty acid, glycerol, ammonia, urea and potassium concentrations had increased from resting values by the end of the test (P < 0.05). In conclusion, the results of this study suggest that endurance-trained wheelchair athletes are able to maintain velocities equivalent to the same relative exercise intensity (75% VO2peak) for prolonged periods irrespective of lesion level.